A review on the accumulation of heavy metals in coastal sediment of Peninsular Malaysia - Yunus, Kamaruzzaman; M.A, Zuraida; John, Akbar (Emerald, 2020)
Purpose – This study aims to examine the metal pollution in coastal sediment in the Peninsular Malaysia. Design/methodology/approach – Approximately 141 published studies were screened from 1,285 documents and reviewed to determine the existing pollution status in the coastal areas of Peninsular Malaysia and the metals under review were Pb, Hg, Cd, Ar, Cu, Zn, Cr and Ni. Sources of pollutants and their effect on biological systems, marine organisms and human health were addressed in this review as well as recommendation of heavy metal removal or remedies in short. Emphasis is placed on marine pollution, particularly on the toxic metal accumulation in biota. Findings – This study has revealed the different concentrations of pollutants, low, moderately, and chronically contaminated areas from heavy metals and the consequences to aquatic ecosystem and indirectly to human health, since an increasing in the coastal developments in Peninsular Malaysia. Originality/value – This study has revealed the different concentrations of pollutants, low, moderately, and chronically contaminated areas from heavy metals and the consequences to aquatic ecosystem and indirectly to human health, since an increasing in the coastal developments in Peninsular Malaysia.